Protective effect of interferon-based antiviral therapy on risk of bipolar disorder in patients with hepatitis C Virus infection: A nationwide longitudinal study - Mu- Hong Chen; Shih- Jen Tsai; Tzeng- Ji Chen (Taiwanese Journal of Psychiatry, 2022)
Background: A recent study has shown the beneficial effects of interferon (IFN)-based antiviral therapy (AVT) in reducing the risk of newly diagnosed depression among patients with hepatitis C virus (HCV) infection. But whether IFN-based AVT reduces the risk of bipolar disorder remains unknown. Methods: This is a retrospective study based on the Taiwan National Health Insurance Research Database. From enrollment to the end of 2013, 24,240 patients with HCV infection (4473 treated with IFN-based AVT and 19,767 without such treatment) as well as 96,960 age- and sex-matched controls were included in this study. Time-dependent Cox regression models were used to study the differences in risk of newly-diagnosed bipolar disorder between patients being treated with and without IFN-based AVT and the control participants. Results: Patients with HCV infection who had not yet received IFN-based AVT (hazard ratio = 4.86, 95% confidence interval = 1.87–12.66, p = 0.001), but not those who were receiving IFN-based AVT (1.69, 0.94 - 30.50, nonsignificance) and those who completed the IFN-based AVT (1.77, 0.69 - 4.54, nonsignificance), were significantly more to be diagnosed with bipolar disorder compared with the control group. Conclusion: Our study supports the temporal association between HCV infection and subsequent bipolar disorder, further suggesting that the optimal AVT to eradicate HCV may be associated with a reduced risk of incident bipolar disorder later in life.